2012
DOI: 10.1097/pas.0b013e318242e21c
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal Poorly Differentiated Neuroendocrine Carcinomas and Mixed Adenoneuroendocrine Carcinomas

Abstract: Colorectal poorly differentiated neuroendocrine carcinomas (NECs) and mixed adenoneuroendocrine carcinomas (MANECs) are well-recognized entities generally known to be associated with biological aggressiveness and poor patient survival. However, a few published papers have highlighted the existence of a subgroup of tumors with a better survival than expected; however, to date, there are no established parameters that usefully identify this category. In the present study we have investigated the morphologic feat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
72
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 154 publications
(78 citation statements)
references
References 47 publications
(47 reference statements)
4
72
1
1
Order By: Relevance
“…In the stomach, mixed tumors follow an intermediate behavior between pure large cell NEC, which is the most aggressive subgroup, and conventional gastric adenocarcinoma [25]. In the colon and rectum, the extent of the neuroendocrine component is not a predictor of behavior, and even a minor high-grade neuroendocrine cell population was found able to metastasize [24,26]. Very few cases of hepatobiliary MANEC have been reported so far, and clinical comparisons are still missing [6].…”
Section: Discussionmentioning
confidence: 99%
“…In the stomach, mixed tumors follow an intermediate behavior between pure large cell NEC, which is the most aggressive subgroup, and conventional gastric adenocarcinoma [25]. In the colon and rectum, the extent of the neuroendocrine component is not a predictor of behavior, and even a minor high-grade neuroendocrine cell population was found able to metastasize [24,26]. Very few cases of hepatobiliary MANEC have been reported so far, and clinical comparisons are still missing [6].…”
Section: Discussionmentioning
confidence: 99%
“…As previously described, we fully validated the sensitivity and specificity of these MS-MLPA assays [24,25]. Aberrant methylation was scored as a categorical variable using a specific methylation ratio for each gene corresponding to the highest level of accuracy of the test [25].…”
Section: Methodsmentioning
confidence: 99%
“…Regardless of anatomic site, TP53 alterations have been found to be frequent in NECs (Dacic et al 2002, Furlan et al 2005, together with the impairment of the CDKN2A/p16-Rb pathway (Parwani et al 2003, Nassar et al 2005, Yachida et al 2012. Most GEP-NECs have high chromosomal instability (Furlan et al 2005, Lubensky & Zhuang 2007, while microsatellite instability (MSI) has rarely been observed (Ghimenti et al 1999, Nassar et al 2005, Stelow et al 2006, La Rosa et al 2012a and the role of other epigenetic mechanisms is still poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Although GEP-NECs are generally aggressive cancers, showing ominous prognosis with a median survival (MS) ranging from 6 to 12 months (La Rosa & Sessa 2014), recent findings from a few published studies (Shia et al 2008, Power et al 2010, La Rosa et al 2012a and from anecdotal experience seem to suggest that there is a fraction of patients with GEP-NECs showing a better than expected survival rate. We have recently demonstrated that a subset of colorectal NECs exhibiting MSI and extensive gene hypermethylation showed a better prognosis than NECs without these features (La Rosa et al 2012a,b).…”
Section: Introductionmentioning
confidence: 99%